PENGARUH PENDIDIKAN KESEHATAN TENTANG MENSTRUASI TERHADAP TINGKAT KECEMASAN DALAM MENGHADAPI MENARCHE PADA SISWA KELAS VI SD NEGERI 4 DOBO - Melawati Wakano; Asriaty Dinopawe; Nova Bugis; Siti Nurhidayati; Santika N Gardjalay (Pasapua Health Journal, 2021)
Introduction: Menarche is the first menstrual event as a sign of the onset of puberty in young women. The arrival of menarche actually makes some teenagers anxious and think that menstrual blood is a disease so that it can interfere with the learning process. Objective: Knowing the Effect of Health Education About Menstruation Against Level of Anxiety in Facing Menarche in Grade VI Students of SD Negeri 4 Dobo. Method: Experimental research with a one group pre-test-posttest pre-experimental design. The population in this study were all Grade VI students at SD Negeri 4 Dobo. The sample is students of class VI SD Negeri 4 Dobo, who have not yet menarched, totaling 45 students by using total sampling technique. Results: The average anxiety of Grade VI students at SD Negeri 4 Dobo before being given health education about menstruation in the face of menarche in the moderate category was 27 respondents (60%) and after being given health education about menstruation in facing menarche in the mild category there were 38 respondents (84, 4%). There is an influence of health education about menstruation on the level of anxiety in dealing with menarche in class VI students at SD Negeri 4 Dobo with a significant value of ρ = 0.000. Conclusion: There is an influence of health education about menstruation on Level of Anxiety in Facing Menarche in Grade VI Students of SD Negeri 4 Dobo. Suggestion: These results can be used as material for consideration or alternatives for parties institutions and schools to implement reproductive health education for their students so as not to cause anxiety that will have an impact on the child’s psychology.